Enriched Renewable Methane from the Anaerobic Digestion of Petrochemical Wastewater: A Bio-Remediation Study - Siddique, Md. Nurul Islam; Mohd Fakhrurrazi, Ishak; Zularisam, A. W. (Penerbit Universiti Malaysia Pahang, 2017)
Scarcity of nitrogenous resource and buffering capability were recognized as reverting failure in earlier research treating petrochemical wastewater in anaerobic continuous stirred tank reactors. The purpose of this work is to explore the use of ammonium bicarbonate (NH4HCO3) as supplementation ensuring nitrogenous supply and buffering requirement. With a view to measure the effect of NH4HCO3 on the anaerobic process, a set of dosing up to 40 mg L-1 was examined. The result was evaluated in terms of biogas yield. It was found that 10mgL-1 dosing was the optimal dosing without affecting methanogenesis. Moreover, mathematical calculation explained that this optimum dosing can enhance biogas yield up to 27.77% compared to control PWW digestion. Results showed an obvious financial advantage to make the industrial application feasible.